2020
DOI: 10.1126/science.abe8770
|View full text |Cite
|
Sign up to set email alerts
|

Quantum computational advantage using photons

Abstract: A light approach to quantum advantage Quantum computational advantage or supremacy is a long-anticipated milestone toward practical quantum computers. Recent work claimed to have reached this point, but subsequent work managed to speed up the classical simulation and pointed toward a sample size–dependent loophole. Quantum computational advantage, rather than being a one-shot experimental proof, will be the result of a long-term competition between quantum devices and classical simulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
873
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,695 publications
(952 citation statements)
references
References 69 publications
(118 reference statements)
6
873
0
6
Order By: Relevance
“…Note here that the power ω j is also normalized to be consistent with SOC ∈ [0, 1]. Lastly (7) guarantees that a bus can only be charged continuously, and not intermittently, at most once during each charging window. Hence, the original EV-bus charging problem Eqs 2-7 is an integer programming problem with inequality constraints.…”
Section: Ev-bus Charging Scheduling Problem 21 Problem Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note here that the power ω j is also normalized to be consistent with SOC ∈ [0, 1]. Lastly (7) guarantees that a bus can only be charged continuously, and not intermittently, at most once during each charging window. Hence, the original EV-bus charging problem Eqs 2-7 is an integer programming problem with inequality constraints.…”
Section: Ev-bus Charging Scheduling Problem 21 Problem Definitionmentioning
confidence: 99%
“…In the previous Section 2.3, we have shown that some penalty functions can contain higher-order terms that can not be written into the QUBO objective function, cf. quadratic constraint (7) and the corresponding penalty (11).…”
Section: Limitations Of the Quadratic Penalty Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate goal of implementing a fully faulttolerant quantum error correction scheme for quantum algorithms with provable speed-up may still be years away. However, the recent rapid advance in quantum computing hardware has enabled certain Zhenyu Cai: cai.zhenyu.physics@gmail.com computational tasks to be performed that are well beyond classical capabilities [1,2], prompting the question of whether it is possible to perform any practically useful tasks with the noisy intermediate-scale quantum (NISQ) devices that we will soon have.…”
Section: Introductionmentioning
confidence: 99%
“…A IBM afirmou em um estudo que o problema proposto pelo Google não demoraria 10 mil anos para ser resolvido em uma máquina comum, mas apenas 2 dias e meio se uma técnica diferente fosse utilizada [11]. Ainda neste contexto, pesquisadores chineses relataram em [12] a criação de um computador quântico fotônico, denominado Jiuzhang, segundo os autores, tal computador leva aproximadamente 3 minutos e meio para realizar uma tarefa específica que levaria, segundo estimativa, em um dos melhores supercomputadores clássicos do mundo, o Sunway TaihuLight, cerca de 2,5 bilhões de anos. Alcançando assim a supremacia quântica.…”
Section: Introductionunclassified